Designing Mobile Game “Tebak Kata Inggris” as the Media of Teaching Vocabulary for Primary School Students: A Development Research for Four Grade Students in SD Integral Luqman Al-Hakim Pontianak - Agus Supriadi; Gatot Sutapa; Clarry Sada (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study explores the development of an Android-based mobile game application,